Carbon-coated current collector for inhibiting thermal deformation as well as preparation method and application of carbon-coated current collector

By adding expanded microspheres to the carbon-coated current collector, the thermal expansion and contraction characteristics are utilized to actively offset thermal stress, thus solving the thermal deformation problem of lithium-ion battery current collectors, improving battery safety and performance stability, and making it suitable for industrial applications in lithium battery production lines.

CN121506961APending Publication Date: 2026-02-10YANGZHOU NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511653211.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-12
Publication Date
2026-02-10

AI Technical Summary

Technical Problem

Traditional lithium-ion battery current collectors suffer from thermal deformation due to their metal-polymer heterostructure, leading to safety risks, performance degradation, and structural reliability issues. Existing technologies have failed to effectively suppress thermal stress, hindering the large-scale application of composite current collectors.

Method used

Expandable microspheres are added to the carbon coating layer of the carbon-coated current collector to actively offset thermal stress by utilizing their thermal expansion and contraction characteristics. The expansion of the core of the microspheres expands when the current collector is heated and shrinks when cooled to achieve deformation recovery, reducing the risk of interface peeling. The heat resistance of the carbon coating layer is enhanced by the polyacrylic acid shell.

Benefits of technology

It effectively suppresses thermal deformation, improves battery safety and performance stability, reduces interface resistance, improves thermomechanical properties, and is compatible with existing lithium battery production lines without requiring process changes, thus reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of battery manufacturing, and relates to a carbon-coated current collector capable of inhibiting thermal deformation and a preparation method and application thereof.The carbon-coated current collector comprises a current collector base material and a carbon-coated layer arranged on the surface of at least one side of the current collector base material, and the carbon-coated layer at least contains expanded microspheres; and the expansion microsphere is composed of a polyolefin acid shell and internal organic gas. The expansion microspheres are added in the carbon-coated layer of the carbon-coated current collector, thermal stress is actively counteracted by utilizing the thermal expansion and cold contraction characteristics of the expansion microspheres, so that the thermal deformation phenomenon is inhibited, meanwhile, the safety and the performance stability are considered, and the industrial popularization requirements are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery manufacturing technology, and relates to a carbon-coated current collector, and more particularly to a carbon-coated current collector that inhibits thermal deformation, its preparation method and application. Background Technology

[0002] Against the backdrop of the rapid development of the new energy industry, lithium-ion batteries (LIBs) have become the core energy carrier for consumer electronics, electric vehicles, and large-scale energy storage systems due to their advantages such as high energy density and long cycle life. As the performance requirements for batteries continue to upgrade across various application scenarios—from the miniaturization and fast charging of consumer electronics to the long-range and high safety demands of electric vehicles, and the long-term stable operation of energy storage systems—more stringent performance standards are being placed on the core components of lithium-ion batteries. Among these, the current collector, as a key component for current collection and structural support within the battery, has seen its performance optimization become a crucial breakthrough for improving the overall quality of the battery.

[0003] Traditional lithium-ion battery current collectors are mainly made of pure aluminum foil and pure copper foil. However, these single-metal current collectors have limitations such as high density, insufficient flexibility, and high cost, making it difficult to meet the development trends of lightweight, thin, and low-cost batteries. To solve this problem, the industry has gradually developed composite current collector technology, which combines metal foil (aluminum foil, copper foil) with polymer substrates (such as polyethylene, polypropylene film), paper-based materials, or functional coatings to form a composite structure that combines the conductivity of metals with the lightweight and high toughness of polymer materials. Among them, carbon-coated composite current collectors have become a hot research and application area because they can further improve battery rate performance and interface stability. This is because the carbon coating layer can reduce the contact resistance between the current collector and the active material, optimize the lithium-ion transport path, and thus improve the battery's charge and discharge efficiency and cycle life. It has already been widely used in mid-to-high-end lithium-ion battery products.

[0004] However, the heterogeneous "metal-polymer" structure of composite current collectors leads to severe thermodynamic performance imbalances and insufficient interfacial stability. This core contradiction is further amplified during battery fabrication (such as oven baking to dry the carbon coating) and actual service (heat generation during charging and discharging), ultimately causing significant thermal deformation risks and becoming a key bottleneck restricting the large-scale application of carbon-coated composite current collectors. From a thermodynamic perspective, the thermal expansion coefficients of metal substrates (such as aluminum foil) and polymer substrates differ by 1-2 orders of magnitude. Upon temperature change, their volume deformation is drastically different, resulting in enormous thermal stress within the composite current collector. Simultaneously, the interfacial bonding between the carbon coating and the metal / polymer substrate is weak, making the carbon coating prone to peeling and cracking due to thermal stress, further exacerbating structural instability.

[0005] This thermal deformation problem directly leads to three serious consequences: First, safety risks. Thermal deformation can easily cause wrinkles and cracks in the composite current collector, damaging the insulation performance of the battery's internal separator, causing direct contact between the positive and negative electrodes, leading to internal short circuits, and even triggering fires and explosions. This poses a significant threat to scenarios with extremely high safety requirements, such as electric vehicles and energy storage systems. Second, performance degradation risks. Peeling of the carbon coating and interface cracking significantly increase the interface resistance, leading to increased energy loss and decreased energy efficiency during battery charging and discharging. It also damages lithium-ion transport channels, shortening battery cycle life. Third, structural reliability risks. The instability of the composite current collector's mechanical structure caused by thermal deformation can lead to cell expansion, bulging, or even breakage, reducing the consistency and structural strength of the battery assembly, affecting the long-term service reliability of the battery module, and increasing subsequent maintenance costs.

[0006] Current industry optimization efforts for composite current collectors primarily focus on improving the conductivity of the carbon coating layer and optimizing the bonding strength of the composite substrate. However, no technological solution has yet addressed these issues by actively mitigating thermal stress and suppressing thermal deformation. Therefore, developing a technical strategy that can specifically alleviate the thermal deformation of composite current collectors while balancing safety and performance stability is a key requirement for overcoming current technological bottlenecks and promoting the large-scale application of carbon-coated composite current collectors in demanding scenarios. Summary of the Invention

[0007] To address the shortcomings of existing technologies, the present invention aims to provide a carbon-coated current collector that suppresses thermal deformation, its preparation method, and its application. By adding expanded microspheres to the carbon coating layer of the carbon-coated current collector, the thermal expansion and contraction characteristics are utilized to actively offset thermal stress, thereby suppressing thermal deformation. At the same time, it takes into account both safety and performance stability, meeting the needs of industrial promotion.

[0008] To achieve this objective, the present invention adopts the following technical solution:

[0009] In a first aspect, the present invention provides a carbon-coated current collector that suppresses thermal deformation, comprising a current collector substrate and a carbon coating layer disposed on at least one surface of the current collector substrate, wherein the carbon coating layer contains at least expanded microspheres, and the expanded microspheres are composed of a polyacrylate shell and an internal organic gas.

[0010] This invention adds expandable microspheres to the carbon coating layer of a carbon-coated current collector. When the current collector is heated, the core of the microspheres vaporizes, causing volume expansion. The stress generated by the current collector directly acts on the expandable microspheres, achieving stress cancellation. When the current collector cools, the expandable microspheres shrink in volume, undergoing elastic deformation, and the deformation of the current collector recovers accordingly, effectively reducing the risk of interfacial delamination between the carbon coating layer and the current collector substrate. In short, the thermal expansion and contraction characteristics of the expandable microspheres actively counteract thermal stress, thereby suppressing thermal deformation.

[0011] In addition, the polyacrylic acid shell of the expanded microspheres has good thermal stability, which can enhance the heat resistance of the carbon coating layer. When the microspheres are uniformly dispersed, they can effectively inhibit the crack propagation phenomenon in the carbon coating layer, thereby improving the thermomechanical properties of the carbon coating layer.

[0012] Preferably, the carbon coating layer further contains a binder, a conductive agent, a pH adjuster, and a wetting agent.

[0013] Preferably, the amount of expanded microspheres added is 2.5%-5.0% of the mass of the conductive agent.

[0014] Preferably, the polymeric monomers of the polyacrylic acid shell include acrylic acid and / or methyl methacrylate.

[0015] Preferably, the internal organic gas includes isobutane.

[0016] Preferably, the method for preparing the expanded microspheres includes the following steps:

[0017] (1) Mix deionized water and emulsifier, stir until completely dissolved, and adjust the pH to alkaline to obtain an aqueous solution;

[0018] (2) Mix polyacrylic acid monomer, crosslinking agent and foaming agent, and stir evenly to obtain an oil phase solution;

[0019] (3) The oil phase solution is added to the aqueous phase solution for shear emulsification to obtain a stable emulsion. Then, an inert gas is introduced into the emulsion and the temperature is raised. An initiator is added to carry out a polymerization reaction. Finally, an inhibitor is added to terminate the reaction to obtain a reactive emulsion.

[0020] (4) Adjust the pH of the reaction emulsion to acidic to break the emulsion, and obtain expanded microspheres after solid-liquid separation, washing and drying.

[0021] Preferably, the emulsifier in step (1) includes sodium dodecyl sulfate, and the amount used is 1%-3% of the mass of the aqueous solution.

[0022] Preferably, the pH adjuster used in step (1) includes sodium bicarbonate, and the pH is adjusted to 7-9.

[0023] Preferably, the polyacrylate monomer in step (2) includes acrylic acid and / or methyl methacrylate.

[0024] Preferably, the crosslinking agent in step (2) comprises divinylbenzene, and the amount used is 0.5%-2% of the mass of the oil phase solution.

[0025] Preferably, the foaming agent in step (2) includes isobutane, and the amount used is 10%-30% of the mass of polyacrylic acid monomer.

[0026] Preferably, the shear rate of the shear emulsification in step (3) is 1000-3000 rpm and the emulsification time is 10-20 min.

[0027] Preferably, the inert gas in step (3) includes at least one of nitrogen, argon or helium.

[0028] Preferably, the target temperature for heating in step (3) is 60-80℃.

[0029] Preferably, the initiator in step (3) includes potassium persulfate, and the amount used is 0.5%-1% of the mass of the polyacrylic acid monomer.

[0030] Preferably, the polymerization reaction in step (3) takes 4-8 hours until the polyacrylate monomer conversion rate is ≥95%.

[0031] Preferably, the pH of the reaction emulsion in step (4) is adjusted using a hydrochloric acid solution.

[0032] Preferably, the solid-liquid separation method in step (4) includes centrifugation, the washing uses deionized water, and the drying method includes vacuum drying.

[0033] In a second aspect, the present invention provides a method for preparing a carbon-coated current collector as described in the first aspect, comprising the following steps:

[0034] S1. Mix deionized water and binder, then add some conductive agent for the first dispersion treatment;

[0035] S2. Add the remaining conductive agent for a second dispersion treatment, then add deionized water for a third dispersion treatment;

[0036] S3. Add pH adjuster until the slurry is weakly acidic, then add expanded microspheres for the fourth dispersion treatment;

[0037] S4. Add wetting agent for the fifth dispersion treatment, and then homogenize the material after discharge.

[0038] S5. The homogenized slurry is uniformly coated on at least one side of the current collector substrate and dried to obtain a carbon-coated current collector.

[0039] The preparation method provided by this invention is based on the improvement of the existing carbon coating current collector process. It is achieved by adding expanded microspheres and adjusting the slurry formula. It does not require changing the existing battery production process or adding special equipment. It can be directly adapted to lithium battery production lines, with low production and maintenance costs, strong practicality, and meets the needs of industrial promotion.

[0040] Preferably, the adhesive in step S1 comprises polyacrylic acid liquid with a solid content of 15-30 wt% and a viscosity of 800-3500 mPa·s.

[0041] Preferably, the conductive agent in steps S1 and S2 includes carbon powder and / or graphite powder, and the amount of conductive agent added in steps S1 and S2 is 40%-70% of the total amount of conductive agent.

[0042] Preferably, the pH adjuster in step S3 includes a sodium hydroxide solution, which is added to the slurry to achieve a pH of 5-7.

[0043] Preferably, the wetting agent in step S4 includes at least one of polyether siloxane, modified polyether siloxane, or isopropanol, and more preferably modified polyether siloxane.

[0044] Preferably, the first dispersion treatment, the second dispersion treatment, the third dispersion treatment, the fourth dispersion treatment and the fifth dispersion treatment are carried out in a double-star stirred tank.

[0045] Preferably, the stirring rate of the first dispersion treatment is 2000-2600 rpm, and the stirring time is 20-40 min.

[0046] Preferably, the stirring rate of the second dispersion treatment is 2000-2600 rpm, and the stirring time is 40-80 min.

[0047] Preferably, the stirring rate of the third dispersion treatment is 2000-2600 rpm, and the stirring time is 20-40 min.

[0048] Preferably, the stirring rate of the fourth dispersion treatment is 1200-1500 rpm, and the stirring time is 40-80 min.

[0049] Preferably, the stirring rate of the fifth dispersion treatment is 10-15 rpm, and the stirring time is 30-45 min.

[0050] Preferably, the homogenization process is carried out in a homogenizer at a pressure of 200-400 bar and the number of homogenization cycles is 1-3.

[0051] Thirdly, the present invention provides an electrode containing a carbon-coated current collector that inhibits thermal deformation as described in the first aspect.

[0052] Fourthly, the present invention provides a battery comprising a carbon-coated current collector for suppressing thermal deformation as described in the first aspect or an electrode as described in the third aspect.

[0053] Compared with the prior art, the present invention has the following beneficial effects:

[0054] (1) In this invention, expanded microspheres are added to the carbon coating layer of the carbon-coated current collector. When the current collector is heated, the core of the expanded microspheres vaporizes and expands in volume. The stress generated by the current collector is directly applied to the expanded microspheres, thus offsetting the stress. When the current collector cools, the volume of the expanded microspheres shrinks and undergoes elastic deformation. The deformation of the current collector is then restored, effectively reducing the risk of interfacial delamination between the carbon coating layer and the current collector substrate. In short, the thermal expansion and contraction characteristics of the expanded microspheres actively offset thermal stress, thereby suppressing thermal deformation.

[0055] (2) The polyacrylic acid shell of the expanded microspheres has good thermal stability, which can enhance the heat resistance of the carbon coating layer. When the microspheres are evenly dispersed, they can effectively inhibit the crack propagation phenomenon in the carbon coating layer, thereby improving the thermomechanical properties of the carbon coating layer.

[0056] (3) The preparation method provided by the present invention is based on the improvement of the existing carbon coating current collector process. It is achieved by adding expanded microspheres and adjusting the slurry formula. It does not require changing the existing battery production process or adding special equipment. It can be directly adapted to the lithium battery industry production line. The production and maintenance costs are low, and it is highly practical and meets the needs of industrial promotion. Detailed Implementation

[0057] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0058] One embodiment of the present invention provides a carbon-coated current collector that suppresses thermal deformation, comprising a current collector substrate and a carbon coating layer disposed on at least one side surface of the current collector substrate, wherein the carbon coating layer contains at least expanded microspheres, and the expanded microspheres are composed of a polyacrylate shell and an internal organic gas.

[0059] This invention adds expandable microspheres to the carbon coating layer of a carbon-coated current collector. When the current collector is heated, the core of the microspheres vaporizes, causing volume expansion. The stress generated by the current collector directly acts on the expandable microspheres, achieving stress cancellation. When the current collector cools, the expandable microspheres shrink in volume, undergoing elastic deformation, and the deformation of the current collector recovers accordingly, effectively reducing the risk of interfacial delamination between the carbon coating layer and the current collector substrate. In short, the thermal expansion and contraction characteristics of the expandable microspheres actively counteract thermal stress, thereby suppressing thermal deformation.

[0060] Specifically, the outer shell of the expandable microspheres is made of thermoplastic polyacrylate, and the core is an organic gas. When heated to the trigger temperature (typically 80-150℃), the core vaporizes, and the microspheres expand in volume by 5-50 times. Simultaneously, when the current collector is heated, the metal substrate expands, and the carbon coating layer, due to its low coefficient of expansion, experiences shrinkage stress. At this point, due to the expansion of the microspheres, the radial expansion force offsets the shrinkage stress of the carbon coating layer, thereby reducing the risk of interfacial delamination between the carbon coating layer and the current collector substrate. Furthermore, the expansion direction of the microspheres is adjustable (related to the degree of cross-linking of the outer shell), preferentially expanding along the plane of the carbon coating layer, thus avoiding the impact of vertical thickness variations on conductivity.

[0061] In addition, after expansion, the microspheres can form a uniform closed-cell structure with a porosity of 5%-30%. Since the porous structure has a lower elastic modulus, it can act as a buffer like a "spring", fully absorbing the thermal stress between the metal substrate and the carbon coating layer. At the same time, it reduces the overall expansion coefficient of the carbon coating layer and reduces the mismatch between its expansion coefficient and that of the metal substrate, thereby effectively alleviating the problem of thermodynamic performance imbalance.

[0062] Furthermore, the polyacrylic acid shell of the expanded microspheres itself has good thermal stability, which can enhance the heat resistance of the carbon coating layer. When the microspheres are uniformly dispersed, they can effectively inhibit the crack propagation phenomenon in the carbon coating layer, thereby improving the thermomechanical properties of the carbon coating layer.

[0063] In some embodiments, the carbon coating layer also contains a binder, a conductive agent, a pH adjuster, and a wetting agent.

[0064] In some embodiments, the amount of expanded microspheres added is 2.5%-5.0% of the mass of the conductive agent, for example, it can be 2.5%, 3.0%, 3.5%, 4.0%, 4.5% or 5.0%, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0065] In some embodiments, the polymeric monomers of the polyacrylic acid shell include acrylic acid and / or methyl methacrylate.

[0066] In some embodiments, the internal organic gas includes isobutane.

[0067] In some embodiments, the method for preparing the expanded microspheres includes the following steps:

[0068] (1) Mix deionized water and emulsifier, stir until completely dissolved, and adjust the pH to alkaline to obtain an aqueous solution;

[0069] (2) Mix polyacrylic acid monomer, crosslinking agent and foaming agent, and stir evenly to obtain an oil phase solution;

[0070] (3) The oil phase solution is added to the aqueous phase solution for shear emulsification to obtain a stable emulsion. Then, an inert gas is introduced into the emulsion and the temperature is raised. An initiator is added to carry out a polymerization reaction. Finally, an inhibitor is added to terminate the reaction to obtain a reactive emulsion.

[0071] (4) Adjust the pH of the reaction emulsion to acidic to break the emulsion, and obtain expanded microspheres after solid-liquid separation, washing and drying.

[0072] In some embodiments, the emulsifier in step (1) includes sodium dodecyl sulfate, and the amount used is 1%-3% of the mass of the aqueous solution, for example, it can be 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8% or 3%, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0073] In some embodiments, the pH adjuster used in step (1) includes sodium bicarbonate, and the pH is adjusted to 7-9, for example, 7, 7.2, 7.4, 7.6, 7.8, 8, 8.2, 8.4, 8.6, 8.8 or 9, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0074] In step (1), the pH of the aqueous solution is adjusted to alkaline, which can effectively prevent the polyacrylic acid monomers added later from polymerizing prematurely.

[0075] In some embodiments, the polyacrylate monomer in step (2) includes acrylic acid and / or methyl methacrylate.

[0076] In some embodiments, the crosslinking agent in step (2) includes divinylbenzene, and the amount used is 0.5%-2% of the mass of the oil phase solution. For example, it can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0077] In some embodiments, the foaming agent in step (2) includes isobutane, and the amount used is 10%-30% of the mass of the polyacrylic acid monomer, for example, it can be 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28% or 30%, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0078] In some embodiments, the shear rate of the shear emulsification in step (3) is 1000-3000 rpm, for example, it can be 1000 rpm, 1200 rpm, 1400 rpm, 1600 rpm, 1800 rpm, 2000 rpm, 2200 rpm, 2400 rpm, 2600 rpm, 2800 rpm or 3000 rpm, and the emulsification time is 10-20 min, for example, it can be 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min or 20 min, but it is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0079] In some embodiments, the inert gas in step (3) includes at least one of nitrogen, argon, or helium.

[0080] The present invention introduces an inert gas into the emulsion to remove oxygen, which can prevent the polymerization inhibition effect of oxygen and facilitate the smooth progress of subsequent polymerization reactions.

[0081] In some embodiments, the target temperature for heating in step (3) is 60-80°C, for example, it can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0082] In some embodiments, the initiator in step (3) includes potassium persulfate, and the amount used is 0.5%-1% of the mass of the polyacrylic acid monomer, for example, it can be 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95% or 1%, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0083] In some embodiments, the polymerization reaction time in step (3) is 4-8 hours, for example, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours or 8 hours, until the polyacrylate monomer conversion rate is ≥95%, for example, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5% or 99%, but not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0084] In this invention, the conversion rate of the polyacrylic acid monomer can be monitored by FTIR or gas chromatography.

[0085] In some embodiments, the pH of the reaction emulsion in step (4) is adjusted using a hydrochloric acid solution.

[0086] In some embodiments, the solid-liquid separation method in step (4) includes centrifugation, the washing method uses deionized water, and the drying method includes vacuum drying.

[0087] In some embodiments, the number of washes is 3-5 times, for example, 3 times, 4 times or 5 times.

[0088] In some embodiments, the drying temperature is 40-50°C, for example, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0089] One embodiment of the present invention also provides a method for preparing the carbon-coated current collector described in any of the above embodiments, comprising the following steps:

[0090] S1. Mix deionized water and binder, then add some conductive agent for the first dispersion treatment;

[0091] S2. Add the remaining conductive agent for a second dispersion treatment, then add deionized water for a third dispersion treatment;

[0092] S3. Add pH adjuster until the slurry is weakly acidic, then add expanded microspheres for the fourth dispersion treatment;

[0093] S4. Add wetting agent for the fifth dispersion treatment, and then homogenize the material after discharge.

[0094] S5. The homogenized slurry is uniformly coated on at least one side of the current collector substrate and dried to obtain a carbon-coated current collector.

[0095] The preparation method provided by this invention is based on the improvement of the existing carbon coating current collector process. It is achieved by adding expanded microspheres and adjusting the slurry formula. It does not require changing the existing battery production process or adding special equipment. It can be directly adapted to lithium battery production lines, with low production and maintenance costs, strong practicality, and meets the needs of industrial promotion.

[0096] In some embodiments, the adhesive in step S1 comprises a polyacrylic acid liquid with a solid content of 15-30 wt%, for example, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, 20 wt%, 21 wt%, 22 wt%, 23 wt%, 24 wt%, 25 wt%, 26 wt%, 27 wt%, 28 wt%, 29 wt%, or 30 wt%, and a viscosity of 800-3500 mPa·s, for example, 800 mPa·s. 1000 mPa.s, 1200 mPa.s, 1400 mPa.s, 1600 mPa.s, 1800 mPa.s, 2000 mPa.s, 2200 mPa.s, 2400 mPa.s, 2600 mPa.s, 2800 mPa.s, 3000 mPa.s, 3200 mPa.s, 3400 mPa.s, or 3500 mPa.s, but not limited to the listed values; other unlisted values ​​within this range also apply.

[0097] In some embodiments, the conductive agent in steps S1 and S2 includes carbon powder and / or graphite powder, and the amount of conductive agent added in steps S1 and S2 is 40%-70% of the total amount of conductive agent, for example, it can be 40%, 45%, 50%, 55%, 60%, 65% or 70%, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0098] In some embodiments, the pH adjuster in step S3 includes a sodium hydroxide solution, which is added to the slurry at a pH of 5-7. For example, it can be 5, 5.2, 5.4, 5.6, 5.8, 6, 6.2, 6.4, 6.6, 6.8 or 7, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0099] In some embodiments, the wetting agent in step S4 includes at least one of polyether siloxane, modified polyether siloxane, or isopropanol, more preferably modified polyether siloxane.

[0100] In some embodiments, the first dispersion treatment, the second dispersion treatment, the third dispersion treatment, the fourth dispersion treatment, and the fifth dispersion treatment are carried out in a double-star stirred tank.

[0101] In some embodiments, the stirring rate of the first dispersion treatment is 2000-2600 rpm, for example, 2000 rpm, 2100 rpm, 2200 rpm, 2300 rpm, 2400 rpm, 2500 rpm or 2600 rpm, and the stirring time is 20-40 min, for example, 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, 32 min, 34 min, 36 min, 38 min or 40 min, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0102] In some embodiments, the stirring rate of the second dispersion treatment is 2000-2600 rpm, for example, 2000 rpm, 2100 rpm, 2200 rpm, 2300 rpm, 2400 rpm, 2500 rpm or 2600 rpm, and the stirring time is 40-80 min, for example, 40 min, 45 min, 50 min, 55 min, 60 min, 65 min, 70 min, 75 min or 80 min, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0103] In some embodiments, the stirring rate of the third dispersion treatment is 2000-2600 rpm, for example, 2000 rpm, 2100 rpm, 2200 rpm, 2300 rpm, 2400 rpm, 2500 rpm or 2600 rpm, and the stirring time is 20-40 min, for example, 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, 32 min, 34 min, 36 min, 38 min or 40 min, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0104] In some embodiments, the stirring rate of the fourth dispersion treatment is 1200-1500 rpm, for example, 1200 rpm, 1250 rpm, 1300 rpm, 1350 rpm, 1400 rpm, 1450 rpm or 1500 rpm, and the stirring time is 40-80 min, for example, 40 min, 45 min, 50 min, 55 min, 60 min, 65 min, 70 min, 75 min or 80 min, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0105] In some embodiments, the stirring rate of the fifth dispersion treatment is 10-15 rpm, for example, 10 rpm, 11 rpm, 12 rpm, 13 rpm, 14 rpm or 15 rpm, and the stirring time is 30-45 min, for example, 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min, 40 min, 41 min, 42 min, 43 min, 44 min or 45 min, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0106] In some embodiments, the homogenization process is carried out in a homogenizer at a pressure of 200-400 bar, such as 200 bar, 220 bar, 240 bar, 260 bar, 280 bar, 300 bar, 320 bar, 340 bar, 360 bar, 380 bar, or 400 bar, and the number of homogenization cycles is 1-3, such as 1, 2, or 3 times, but not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0107] One embodiment of the present invention also provides an electrode containing the carbon-coated current collector for suppressing thermal deformation as described in any of the above embodiments.

[0108] One embodiment of the present invention also provides a battery containing a carbon-coated current collector for suppressing thermal deformation as described in any of the above embodiments or an electrode as described in any of the above embodiments.

[0109] The numerical range described in this invention includes not only the point values ​​listed above, but also any point values ​​within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values ​​included in the range.

[0110] Preparation Example

[0111] This preparation example prepares an expanded microsphere, using the following raw materials:

[0112] ① Sodium dodecyl sulfate, purchased from Sinopharm Group, model: CP (Shanghai Test), 500g, Sinopharm code 30166428;

[0113] ② Sodium bicarbonate, purchased from Sinopharm Group, model: AR (Shanghai Trial), ≥99.5%, 500g, Sinopharm code 10018960;

[0114] ③ Acrylic acid, purchased from Sinopharm Group, model: AR (Shanghai Test), ≥99.0%, 500mL, Sinopharm code 80001418;

[0115] ④ Methyl methacrylate, purchased from Sinopharm Group, model: GCS (Wokai), ≥99.5%, 5mL, Sinopharm code 40160861;

[0116] ⑤ Isobutane, purchased from Sinopec, type: industrial grade isobutane (purity ≥99.5%).

[0117] ⑥ Potassium persulfate, purchased from Sinopharm Group, model: AR (Shanghai Test), ≥99.5%, 500g, Sinopharm code 10017418;

[0118] ⑦ Divinylbenzene, purchased from Jiangsu Runfeng Synthetic Chemical Co., Ltd., model: DVB-80 (80% divinylbenzene, containing ethylvinylbenzene).

[0119] The preparation method of expanded microspheres includes the following steps:

[0120] (1) Pre-emulsification stage (aqueous phase preparation): Add deionized water to the reactor, then add sodium dodecyl sulfate as an emulsifier at a rate of 2% of the solution mass. Stir magnetically at 600 rpm for 15 minutes until completely dissolved. Then add sodium bicarbonate as a pH adjuster to adjust the pH to 8±1 to obtain an aqueous phase solution.

[0121] (2) Preparation of oil phase: Mix polyacrylic acid monomer (50wt% acrylic acid + 50wt% methyl methacrylate) and crosslinking agent (divinylbenzene), stir at 1000 rpm for 80 min, and the amount of crosslinking agent is 1.5% of the solution mass. Then add foaming agent (isobutane) at 20% of the polyacrylic acid monomer mass. Avoid volatilization at low temperature (<10℃). After stirring evenly, the oil phase solution is obtained.

[0122] (3) Emulsion polymerization reaction: The oil phase solution is slowly added to the aqueous phase solution, and high-speed shear emulsification is carried out at a rate of 2000 rpm for 15 min to form a stable emulsion. Then, nitrogen gas is introduced to remove oxygen, the temperature is raised to 70℃, and an initiator (potassium persulfate) is added at a rate of 0.8% of the mass of polyacrylic acid monomer. The reaction is kept at a constant temperature for 6 h until the conversion rate of polyacrylic acid monomer is ≥95%. The reaction is cooled to room temperature, and a small amount of polymerization inhibitor is added to terminate the reaction to obtain the reaction emulsion.

[0123] (4) Post-treatment (demulsification and washing): Add hydrochloric acid solution to adjust the pH of the reaction emulsion to acidic for demulsification, centrifuge to separate the microspheres, wash with deionized water 4 times to remove residual emulsifier, and vacuum dry at 45°C to obtain white powdery expanded microspheres.

[0124] Example 1

[0125] This embodiment provides a carbon-coated current collector that inhibits thermal deformation and its preparation method. The required raw materials are as follows:

[0126] ① Acrylic acid, purchased from Sinopharm Group, model: AR (Shanghai Test), ≥99.0%, 500mL, Sinopharm code 80001418;

[0127] ② Carbon black, purchased from Imerys, Belgium, type: Super P Li;

[0128] ③ Graphite, Qingdao Heilong Graphite, model: HLG-805;

[0129] ④ Sodium hydroxide, purchased from Sinopharm Group, model: AR (Shanghai Trial), ≥96.0%, 500g, Sinopharm code 10019718.

[0130] The preparation method of the carbon-coated current collector includes the following steps:

[0131] S1. Mix deionized water and polyacrylic acid adhesive (solid content 24wt%, viscosity 2200mPa.s), then add half carbon black and half graphite, and disperse at high speed of 2300rpm for 30min in a 200L double star stirring tank.

[0132] S2. Add the other half of carbon black and the other half of graphite, and disperse at high speed of 2300 rpm for 60 min in a 200L double star stirring tank. Then add deionized water and disperse at high speed of 2300 rpm for 30 min in a 200L double star stirring tank.

[0133] S3. Add 0.5 mM sodium hydroxide solution until the pH of the slurry is 6 ± 1 (weakly acidic), then add the expanded microspheres obtained in the preparation example, the amount of which is 5% of the total mass of carbon black and graphite, and disperse in a 200 L double star stirring tank at 1300 rpm for 60 min.

[0134] S4. Add isopropanol as a wetting agent at a dosage of 10% of the total mass of the slurry. Disperse the slurry at a low speed of 12 rpm for 40 min in a 200L double-star mixing tank. After discharge, homogenize the slurry twice in a homogenizer at a pressure of 300 bar.

[0135] S5. The homogenized slurry is evenly coated on both sides of the current collector substrate, and the coating thickness is controlled to be 1μm. After drying, the carbon-coated current collector is obtained.

[0136] Example 2

[0137] This embodiment provides a carbon-coated current collector that inhibits thermal deformation and its preparation method. Except for changing the amount of expanded microspheres in step S3 to 2.5% of the total mass of carbon black and graphite, the other steps and conditions are the same as in Example 1.

[0138] Example 3

[0139] This embodiment provides a carbon-coated current collector that inhibits thermal deformation and its preparation method. Except for changing the amount of expanded microspheres in step S3 to 1% of the total mass of carbon black and graphite, the other steps and conditions are the same as in Example 1.

[0140] Example 4

[0141] This embodiment provides a carbon-coated current collector that inhibits thermal deformation and its preparation method. Except for changing the amount of expanded microspheres in step S3 to 6% of the total mass of carbon black and graphite, the other steps and conditions are the same as in Example 1.

[0142] Example 5

[0143] This embodiment provides a carbon-coated current collector that inhibits thermal deformation and its preparation method. Except for replacing the wetting agent in step S4 with polyether siloxane, the other steps and conditions are the same as in Example 1.

[0144] Comparative Example 1

[0145] This comparative example provides a carbon-coated current collector and its preparation method. Except that a pH adjuster was not added in step S3 to make the slurry weakly acidic, the other steps and conditions are the same as in Example 1.

[0146] Comparative Example 2

[0147] This comparative example provides a carbon-coated current collector and its preparation method. Except for the absence of expanded microspheres in step S3, the other steps and conditions are the same as in Example 1.

[0148] Performance testing

[0149] (1) Elongation and tensile strength test: Cut the carbon-coated current collector into strips of 15cm×1.5cm, place the sample on a tensile tester for testing, and record the test parameters.

[0150] (2) Thermodynamic deformation test: Cut the carbon-coated current collector into a square sample of 10cm×10cm, place it on A4 paper, and record the transverse dimension of the sample as A1 and the longitudinal dimension as B1. Then transfer the sample to an oven at 150℃ and bake for 30min. After the sample cools down, take it out and record the transverse dimension of the sample as A2 and the longitudinal dimension as B2. Calculate the transverse thermal deformation rate = (A1-A2) / A1×100% and the longitudinal deformation rate = (B1-B2) / B1×100%.

[0151] The test results of the carbon-coated current collectors obtained in Examples 1-6 and Comparative Examples 1-2 are shown in Table 1 below.

[0152] Table 1

[0153]

[0154] Therefore, this invention adds expanded microspheres to the carbon coating layer of the carbon-coated current collector. When the current collector is heated, the core of the expanded microspheres vaporizes, causing volume expansion. The stress generated by the current collector directly acts on the expanded microspheres, achieving stress cancellation. When the current collector cools, the volume of the expanded microspheres shrinks, undergoing elastic deformation, and the deformation of the current collector recovers accordingly, effectively reducing the risk of interfacial delamination between the carbon coating layer and the current collector substrate. In short, the thermal expansion and contraction characteristics of the expanded microspheres actively cancel thermal stress, thereby suppressing thermal deformation.

[0155] In addition, the polyacrylic acid shell of the expanded microspheres has good thermal stability, which can enhance the heat resistance of the carbon coating layer. When the microspheres are uniformly dispersed, they can effectively inhibit the crack propagation phenomenon in the carbon coating layer, thereby improving the thermomechanical properties of the carbon coating layer.

[0156] Furthermore, the preparation method provided by this invention is based on the improvement of the existing carbon coating current collector process. It is achieved by adding expanded microspheres and adjusting the slurry formula. It does not require changing the existing battery production process or adding special equipment. It can be directly adapted to lithium battery production lines, with low production and maintenance costs, strong practicality, and meets the needs of industrial promotion.

[0157] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A carbon-coated current collector for suppressing thermal deformation, comprising a current collector substrate and a carbon coating layer disposed on at least one surface of the current collector substrate, characterized in that, The carbon coating layer contains at least expanded microspheres, and the expanded microspheres are composed of a polyacrylate shell and an internal organic gas.

2. The carbon-coated current collector for suppressing thermal deformation according to claim 1, characterized in that, The carbon coating layer also contains binders, conductive agents, pH adjusters, and wetting agents; The amount of the expanded microspheres added is 2.5%-5.0% of the mass of the conductive agent. And / or, the polymeric monomers of the polyacrylic acid shell include acrylic acid and / or methyl methacrylate; And / or, the internal organic gas includes isobutane.

3. The carbon-coated current collector for suppressing thermal deformation according to claim 1 or 2, characterized in that, The method for preparing the expanded microspheres includes the following steps: (1) Mix deionized water and emulsifier, stir until completely dissolved, and adjust the pH to alkaline to obtain an aqueous solution; (2) Mix polyacrylic acid monomer, crosslinking agent and foaming agent, and stir evenly to obtain an oil phase solution; (3) The oil phase solution is added to the aqueous phase solution for shear emulsification to obtain a stable emulsion. Then, an inert gas is introduced into the emulsion and the temperature is raised. An initiator is added to carry out a polymerization reaction. Finally, an inhibitor is added to terminate the reaction to obtain a reactive emulsion. (4) Adjust the pH of the reaction emulsion to acidic to break the emulsion, and obtain expanded microspheres after solid-liquid separation, washing and drying.

4. The carbon-coated current collector for suppressing thermal deformation according to claim 3, characterized in that, The emulsifier in step (1) includes sodium dodecyl sulfate, and the amount used is 1%-3% of the mass of the aqueous solution; And / or, the pH adjuster used in step (1) includes sodium bicarbonate, and the pH is adjusted to 7-9; And / or, the polyacrylate monomer in step (2) includes acrylic acid and / or methyl methacrylate; And / or, the crosslinking agent in step (2) comprises divinylbenzene, used in an amount of 0.5%-2% of the mass of the oil phase solution; And / or, the foaming agent in step (2) includes isobutane, used in an amount of 10%-30% of the mass of the polyacrylic acid monomer.

5. The carbon-coated current collector for suppressing thermal deformation according to claim 3, characterized in that, The shear rate of the shear emulsification in step (3) is 1000-3000 rpm, and the emulsification time is 10-20 min; And / or, the inert gas in step (3) includes at least one of nitrogen, argon or helium; And / or, the target temperature for the heating in step (3) is 60-80℃; And / or, the initiator in step (3) includes potassium persulfate, used in an amount of 0.5%-1% of the mass of the polyacrylic acid monomer; And / or, the polymerization reaction in step (3) takes 4-8 hours until the polyacrylate monomer conversion rate is ≥95%; And / or, the pH of the reaction emulsion in step (4) is adjusted using hydrochloric acid solution; And / or, the solid-liquid separation method in step (4) includes centrifugation, the washing uses deionized water, and the drying method includes vacuum drying.

6. A method for preparing a carbon-coated current collector as described in any one of claims 1-5, characterized in that, The preparation method includes the following steps: S1. Mix deionized water and binder, then add some conductive agent for the first dispersion treatment; S2. Add the remaining conductive agent for a second dispersion treatment, then add deionized water for a third dispersion treatment; S3. Add pH adjuster until the slurry is weakly acidic, then add expanded microspheres for the fourth dispersion treatment; S4. Add wetting agent for the fifth dispersion treatment, and then homogenize the material after discharge. S5. The homogenized slurry is uniformly coated on at least one side of the current collector substrate and dried to obtain a carbon-coated current collector.

7. The method for preparing the carbon-coated current collector according to claim 6, characterized in that, The adhesive in step S1 comprises polyacrylic acid liquid with a solid content of 15-30 wt% and a viscosity of 800-3500 mPa·s; And / or, the conductive agent in steps S1 and S2 includes carbon powder and / or graphite powder, and the amount of conductive agent added in steps S1 and S2 is 40%-70% of the total amount of conductive agent, respectively; And / or, the pH adjuster in step S3 includes a sodium hydroxide solution, which is added to the slurry to a pH of 5-7; And / or, the wetting agent in step S4 includes at least one of polyether siloxane, modified polyether siloxane or isopropanol, more preferably modified polyether siloxane.

8. The method for preparing the carbon-coated current collector according to claim 6 or 7, characterized in that, The first dispersion treatment, the second dispersion treatment, the third dispersion treatment, the fourth dispersion treatment, and the fifth dispersion treatment are carried out in a double-star stirred tank. Wherein, the stirring rate of the first dispersion treatment is 2000-2600 rpm, and the stirring time is 20-40 min; And / or, the stirring rate of the second dispersion treatment is 2000-2600 rpm, and the stirring time is 40-80 min; And / or, the stirring rate of the third dispersion treatment is 2000-2600 rpm, and the stirring time is 20-40 min; And / or, the stirring rate of the fourth dispersion treatment is 1200-1500 rpm, and the stirring time is 40-80 min; And / or, the stirring rate of the fifth dispersion treatment is 10-15 rpm, and the stirring time is 30-45 min; And / or, the homogenization process is carried out in a homogenizer at a pressure of 200-400 bar and for 1-3 homogenization cycles.

9. An electrode sheet, characterized in that, The electrode contains a carbon-coated current collector that inhibits thermal deformation as described in any one of claims 1-5.

10. A battery, characterized in that, The battery contains a carbon-coated current collector for suppressing thermal deformation as described in any one of claims 1-5 or an electrode as described in claim 9.